Climate Change and Its Impacts on Saker (Falco cherrug) and Peregrine (Falco peregrinus) Falcons: How the Changes Will Affect Their Migration, Diet, Offspring, and Conservation Efforts - AlAli, Abdulrahman Mubarak; Abbas, Yasmeen Ahmed; Nassar, Farid Saber (Journal of Ecohumanism, 2024)
Climate change is considered as a real danger to many birds including raptors such as the Saker falcons (Falco cherrug) and Peregrine falcons (Falco peregrinus). This article answers the question of how climate change shifts the migration, feeding, and breeding habits of these raptors. These migratory birds keep facing disturbances in their yearly cycle due to recent changes in temperature, precipitation patterns, and pollution. This results in changes in the migration points, as they travel for longer or shorter distances, especially to make their nestlings, and changes in their prey availability, affecting their migration pattern. Also, air pollution affected them significantly, where mercury (Hg) and lead (Pb) levels in their feathers were significantly high. Fortunately, it has not affected their general health yet. As for their reproduction success, it was interrupted, making it necessary to take conservation initiatives and tactics to save these species amid climate-induced alterations by analyzing ecological interconnections and evolutionary mechanisms. The findings highlight the necessity of mitigating climate change effects on migrating raptors to guarantee their survival rate is high and satisfy ecological system equilibrium.